If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7y + 2) = 3x Reorder the terms: (2 + 7y) = 3x Remove parenthesis around (2 + 7y) 2 + 7y = 3x Solving 2 + 7y = 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 7y = -2 + 3x Combine like terms: 2 + -2 = 0 0 + 7y = -2 + 3x 7y = -2 + 3x Divide each side by '7'. y = -0.2857142857 + 0.4285714286x Simplifying y = -0.2857142857 + 0.4285714286x
| 6w^2-12w+8=0 | | x=25/17 | | 64x^2+24-10=0 | | 5/3=w/4-3/4 | | 9/(6x-9)=x/(2x-3)-1/3 | | (9/6x-9)=(x/2x-3)-1/3 | | 9/6x-9=x/2x-3-1/3 | | 4+2+-21= | | 3-4m=9 | | 5x-14y=-13 | | 7x-12y+18z-3x-8y+10z=0 | | 50x=16-24x | | 2y=6x+b | | 4x^2-25y= | | (13x+3)=8x | | X(x+3)=x*x | | 3xy+z=2 | | -2(2n+8)=2 | | -12=9x-(6x-15) | | 56+8x=9x-5 | | y=2(x-3)(x-4) | | F(-x)=9x-6 | | b-47=-8 | | 0.1+0.7x=0.3x^2 | | f(x+9)=9x-6 | | f(2)=9x-6 | | F(f)=0.2F(150) | | r-14=87 | | (33)-20=13 | | (3x-15)/2=4x | | TanA=0.268 | | 4(5x-8)-3(9x-11)=5(2x-3)-12 |